2018
DOI: 10.1002/path.5110
|View full text |Cite
|
Sign up to set email alerts
|

Genetic instability and recurrent MYC amplification in ALK‐translocated NSCLC: a central role of TP53 mutations

Abstract: The anaplastic lymphoma kinase (ALK) rearrangement defines a distinct molecular subtype of non‐small cell lung cancer (NSCLC). Despite the excellent initial efficacy of ALK inhibitors in patients with ALK+ lung cancer, resistance occurs almost inevitably. To date, there is no reliable biomarker allowing the identification of patients at higher risk of relapse. Here, we analysed a subset of 53 ALK+ tumours with and without TP53 mutation and ALK+ NSCLC cell lines by NanoString nCounter technology. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 45 publications
8
40
1
2
Order By: Relevance
“…33 Furthermore, TP53 mutated ALK + lung cancer cells frequently develop amplification of several known cancer genes, including MYC, the overexpression of which not only confers a proliferative advantage per se, but also upregulates EML4-ALK by binding the EML4 promoter. 32 Notably, these secondary effects of TP53 mutations not only promote growth and TKI escape of ALK-driven lung cancer cells, but also represent potential molecular mechanisms for synergy with V3, which is itself associated with stronger oncogenic drive through enhanced ALK phosphorylation, and with relative resistance, i.e. higher IC50 values, against various ALK inhibitors compared to V1 and V2 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…33 Furthermore, TP53 mutated ALK + lung cancer cells frequently develop amplification of several known cancer genes, including MYC, the overexpression of which not only confers a proliferative advantage per se, but also upregulates EML4-ALK by binding the EML4 promoter. 32 Notably, these secondary effects of TP53 mutations not only promote growth and TKI escape of ALK-driven lung cancer cells, but also represent potential molecular mechanisms for synergy with V3, which is itself associated with stronger oncogenic drive through enhanced ALK phosphorylation, and with relative resistance, i.e. higher IC50 values, against various ALK inhibitors compared to V1 and V2 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Both our transcriptomic and epigenomic data point towards MYC as the potential secondary driver in this model. MYC was previously implicated in different ALK dependent malignancies including non-small cell lung cancer (NSCLC) neuroblastoma and ALK+ ALCL (35,(85)(86)(87)(88)(89)(90)). Furthermore, MYC was shown to directly regulate expression of Cdk4 and Cdk6, affecting cell cycle progression at multiple points (91).…”
Section: Discussionmentioning
confidence: 99%
“…Then it was reported that expression of p53 protein could enhance gefitinib-induced apoptosis in NSCLC cells by upregulation of FAS, and TP53 mutations could reduce sensitivity to EGFR-TKI [31,56]. On the other hand, it was assumed that TP53 mutations occurred in the early phase of tumorigenesis could lead to chromosomal instability thereby trigger the development of multiple resistance to targeted therapy [26,30]. For example, in study by Alidousty et al, amplifications of multiple cancer genes including MYC, CCND1, TERT, BIRC2, ORAOV1, YAP1 were observed in 24% of all patients involved in the study who have TP53 and ALK concurrent mutations [30].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was assumed that TP53 mutations occurred in the early phase of tumorigenesis could lead to chromosomal instability thereby trigger the development of multiple resistance to targeted therapy [26,30]. For example, in study by Alidousty et al, amplifications of multiple cancer genes including MYC, CCND1, TERT, BIRC2, ORAOV1, YAP1 were observed in 24% of all patients involved in the study who have TP53 and ALK concurrent mutations [30]. On further investigation, elevated expression levels of the EML4-ALK protein and increased cell proliferation rates were observed due toMYC binding sites within the promoter region of EML4 in ALK+/TP53-mutated cells and MYC-overexpression assuming a potential MYC-dependent resistance mechanism in patients with increased MYC copy numbers, which was in line with conclusions of study by Aisner et al [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation